Pyridoxine in the Treatment of Tetanus Neonatorum - Musa Kazim Caglar (Indonesian Pediatric Society, 1989)
A prospective study has been conducted to assess the efficacy of oral pyridoxine in the treatment of neonatal tetanus. A little reduction in mortality was observed by adding pyridoxine to the conventional therapy. The mortality in this group was 50.0% as compared to 62.5% in controls. This result did not confirm the ones in the literature. This could be sourced from the fact that additional injection was 50.0%.